Cultivating community change to promote food access and healthy eating through participatory action research with youth. Issue 4 (2nd October 2022) - Altares, Ana; Hobbs, Savannah; Sobel, Dana; Nelson, Tracy; Serpa, Magdalena; Bellows, Laura L.
ABSTRACT: Professionals such as social workers, public health officials, cultural networkers, researchers, and community leaders, who are designing and implementing programs and policies, can look to youth to gain a unique perspective on promoting community health. Across the United States, many communities experience inadequate access to nutritious foods that exacerbate poor health outcomes for marginalized populations – people of color, older or disabled adults, and those with lower education or income. To address food access disparities, providing youth voice and building youth empowerment may offer creative strategies to encourage community change. The Youth CAN (Change.Activity.Nutrition) project aimed to engage and empower adolescents to become agents of change for health within their community. Youth became active researchers through participatory action research (PAR) using socially engaged art platforms such as photovoice (photography), street art (graffiti-style art), and spoken word (poetry) to explore their environment and identify facilitators and barriers to healthy eating within their community. The World Café activity facilitated conversation among youth and adults to generate ideas to improve community food access. Collaboration between adult and youth researchers, and community leaders led to proposed solutions for improving access to healthy foods within an urban, low-income neighborhood. The Youth CAN project demonstrated how engaging and empowering youth through PAR is fundamental in promoting positive youth development and enabling youth to become advocates for equitable food access in their communities.